Inter-Organizational Trust: Definitions, Elements and Operationalization - Serje Schmidt (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
Trust management represents a relevant challenge for managers in contexts where the adoption of behaviours that prioritize the satisfaction of individual objectives is prevalent over behaviours directed towards social goods. In this theoretical essay, we propose a review of seminal and contemporary authors on inter-organizational trust. Structuring elements of this phenomena were identified, which allowed the analysis regarding the relevance of its contribution to inter-organizational relationships based on trust. In addition, we reviewed some of the main authors who discuss how to operationalize trust in relationships between organizations. In this article, built in the format of a theoretical essay, it was possible to point out some paths to a theoretical model on inter-organizational trust.